Proposed Pivot Strategy For Point Of Sale System Using Business Model Canvas: A Case Study Of UR POS (PT. RTL) - Senna Haritsyah; Wawan Dhewanto (UNIVED Press, 2025)
This research addresses the challenges faced by UR POS, a unit under PT. Rahmat Tuhan Lestari, as it struggles to keep pace with rapid market changes. Despite the critical role of POS systems in enhancing customer service and operational efficiency, UR POS's traditional business model no longer aligns with current market demands. Using the Business Model Canvas (BMC) and SWOT analysis via the SPACE Matrix, the study identifies 23 strengths, 16 weaknesses, 36 opportunities, and 21 threats. The findings suggest that UR POS should pivot its strategy by focusing on changing customer needs and acquiring new customers. These pivots are then integrated into a new BMC alternative, providing a strategic foundation for adapting and thriving in the evolving market.